Defoliation of sugarcane (Saccharum officinarum) in the Chontalpa, Tabasco, México - Olvera-Rincón, Fabiola (2024)
Introduction. Defoliation studies on sugarcane in Mexico are scarce, and it is unknown at what age of the plant and in which season of the year it should be carried out. Objective. To evaluate the effect of artificial defoliation in sugarcane at different stages of growth and its response on quality and yield parameters. Materials and methods. The experiment was conducted during the 2020-2021 harvest between the months of April and May, in a plot located in a ratoon of the cultivar COLPOSCTMEX 06-039, within the supply area of the Ingenio Presidente Benito Juárez in the Chontalpa region, Tabasco. A completely randomized block design was used, where the defoliation treatments consisted of removing the entire leaves of the stem until leaving the +5 leaf (H5). Defoliation treatments were applied at 8, 9, and 10 months of crop age, plus a control without defoliation, with five replicates per treatment. Growth parameters evaluated were plant height and diameter, number of stalks, and leaf area index (IAF) and normalized difference vegetation index (NDVI). At harvest, °Brix and sugarcane yields of sugarcane were measured. Results. It was found that growth and quality parameters were reduced by total defoliation treatments. Treatment 2 showed the highest values of plant height and diameter, lower NDVI, and stalk yield at harvest, and defoliation affected the IAF. °Brix were not affected by different defoliation treatments. Conclusion. Defoliation at nine months of age increased agricultural yield and did not affect juice quality.